Analisis Kualitas Stimulasi Tumbuh Kembang Anak Didik pada TK PGRI Arrahmah Subahnala Batukliang - Muhammad Iqbal; Lu'luin Najwa; Hasnun Muda Hasan (Universitas Pendidikan Mandalika, 2023)
This study aims at determining the quality of the stimulation of religious and moral aspects, the quality of stimulation of the physical-motor aspect, the quality of stimulation of the cognitive aspect, the quality of stimulation of the language aspect, the quality of stimulation of the social-emotional aspect. This study uses a descriptive qualitative approach. The results of the research are: Stimulation of religious and moral values, namely instilling children to worship Allah, and introducing God's creatures, Physical stimulation for motorized paper folding, Stimulation of cognitive aspects of presenting various objects in the form of works, stimulation of social-emotional aspects such as getting children to queue up, pre-writing activities with a variety of stationery and materials according to age levels through play.